Spectrophotometric intracutaneous analysis for the assessment of burn wounds: A service evaluation of its clinical application in 50 burn wounds. Issue 3 (May 2017) - Tan, A.; Pedrini, F.A.; Oni, G.; Frew, Q.; Philp, B.; Barnes, D.; Dziewulski, P.
Highlights: Non-touch tissue spectrophotometric analysis as new adjunct in burn depth assessment. We carried out a service evaluation on a prototype model (ScanOSkin™). In predicting healing potential, it has a 75% sensitivity and 86% specificity. Benefits include cheaper one off purchase cost, instant images and portability. We feel it has potential as an imaging adjunct in burn depth assessment. Abstract: Introduction: The assessment of burn depth can be challenging even to the experienced burn clinician. Clinical assessment is most widely used to determine burn depth. Because of this subjective nature, various imaging modalities have been invented. The use of photospectometry as a novel technique in burn wound depth analysis has been previously described but the literature is very limited. Methodology: We carried out a single blinded non-randomized comparative study of healing potential of 50 burn wounds between tissue spectrophotometry analysis versus clinical evaluation. Results: ScanOSkin™ technology has an overall sensitivity of 75% and specificity of 86% in predicting healing potential of wounds. Analysis of Inter Rater Agreement (IRA) using Kappa calculations showed strengths of agreement varied from fair to moderate in perfusion and burn depth. IRA for assessing pigmentation however, was poor and this was reflected in user feedback. Conclusion: There is a potential role for ScanOSkin™ tissue spectrophotometric analysis in burn depth assessment. Future studies comparing several imaging modalities with ScanOSkin ®, taking into account costs comparison may be useful for future health resources planning.